2021
DOI: 10.3390/antiox10081294
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Alpha-Lipoic Acid in Viral Infections, including COVID-19

Abstract: Oxidative stress (OS), resulting from a disrupted balance between reactive oxygen species (ROS) and protective antioxidants, is thought to play an important pathogenetic role in several diseases, including viral infections. Alpha-lipoic acid (LA) is one of the most-studied and used natural compounds, as it is endowed with a well-defined antioxidant and immunomodulatory profile. Owing to these properties, LA has been tested in several chronic immunoinflammatory conditions, such as diabetic neuropathy and metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 101 publications
0
28
0
Order By: Relevance
“…A recent study revealed the modulatory action of Lip acid on the course of infection through its antioxidant, anti-inflammatory, and antiviral properties. 17 …”
Section: Introductionmentioning
confidence: 99%
“…A recent study revealed the modulatory action of Lip acid on the course of infection through its antioxidant, anti-inflammatory, and antiviral properties. 17 …”
Section: Introductionmentioning
confidence: 99%
“…Thioctic acid (alpha-lipoic acid, TA) is an oil and water soluble organo-sulfur metabolite that possesses two thiol groups ( Figure 1(B) ). It has been biosynthesized by animals, plants, and humans (Dragomanova et al., 2021 ). Additionally, it existed in supplements and foods and displayed diverse bio-activities such as antioxidant, immuno-modulatory, anti-cancer, anti-aging, anti-inflammatory, antiviral, and neuroprotective activities (Shay et al., 2009 ; Salehi et al., 2019 ; Anthony et al., 2021 ; Dragomanova et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been biosynthesized by animals, plants, and humans (Dragomanova et al., 2021 ). Additionally, it existed in supplements and foods and displayed diverse bio-activities such as antioxidant, immuno-modulatory, anti-cancer, anti-aging, anti-inflammatory, antiviral, and neuroprotective activities (Shay et al., 2009 ; Salehi et al., 2019 ; Anthony et al., 2021 ; Dragomanova et al., 2021 ). It improves utilization of glucose and boosts production of insulin, hence ameliorating hyperglycemia-induced oxidative damage (Salehi et al., 2019 ; Anthony et al., 2021 ; Dragomanova et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations